Strange System of Equations

Algebra Level 5

x x and y y are real numbers satisfying the system of equations { y 2 + 2 y = x 2 2 x + x x + y = 1 2 x \left\{\begin{array}{l}y^2+2y=x^2-2x+\sqrt{x}\\ x+y=\dfrac{1}{2\sqrt{x}}\end{array}\right.

If the value of x y xy can be expressed as a + b c \dfrac{a+\sqrt{b}}{c} for integers a , b , c a,b,c with b b square-free, then what is a + b + c a+b+c ?


The answer is 34.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Daniel Liu
Jun 5, 2014

First, we rearrange the first equation to get y 2 x 2 + 2 x + 2 y = x y^2-x^2+2x+2y=\sqrt{x} which factors into ( y + x ) ( y x + 2 ) = x (y+x)(y-x+2)=\sqrt{x} or y x + 2 = x x + y y-x+2=\dfrac{\sqrt{x}}{x+y}

Now looking at the second equation, we see that x + y = 1 2 x x+y=\dfrac{1}{2\sqrt{x}} Substituting this back into the first equation gives y x + 2 = x 1 2 x = 2 x y-x+2=\dfrac{\sqrt{x}}{\dfrac{1}{2\sqrt{x}}}=2x

Now subtracting the second equation from this new equation gives 2 2 x = 2 x 1 2 x 2-2x=2x-\dfrac{1}{2\sqrt{x}} or 4 x 1 2 x = 2 4x-\dfrac{1}{2\sqrt{x}}=2

Multiplying both sides by x \sqrt{x} gives 4 x x 1 2 = 2 x 4x\sqrt{x}-\dfrac{1}{2}=2\sqrt{x} or 8 x x 4 x 1 = 0 8x\sqrt{x}-4\sqrt{x}-1=0

Substituting z = x z=\sqrt{x} , we have 8 z 3 4 z 1 = 0 8z^3-4z-1=0

Upon inspection with the Rational Root Theorem, we see that 1 2 -\dfrac{1}{2} is a root, thus ( x + 1 2 ) \left(x+\dfrac{1}{2}\right) is a factor. Using synthetic division, we see that 8 z 3 4 z 1 = 2 ( z + 1 2 ) ( 4 z 2 2 z 1 ) 8z^3-4z-1=2\left(z+\dfrac{1}{2}\right)(4z^2-2z-1)

The roots of 4 z 2 2 z 1 4z^2-2z-1 , using the quadratic equation, are z = 1 ± 5 4 z=\dfrac{1\pm \sqrt{5}}{4}

However, see that since z = x z=\sqrt{x} , we must have that z z is positive. Since both z = 1 2 z=-\dfrac{1}{2} and z = 1 5 4 z=\dfrac{1-\sqrt{5}}{4} are negative, we must have z = 1 + 5 4 z=\dfrac{1+\sqrt{5}}{4} .

Thus, x = 1 + 5 4 \sqrt{x}=\dfrac{1+\sqrt{5}}{4} or x = 3 + 5 8 x=\dfrac{3+\sqrt{5}}{8}

Plugging x \sqrt{x} and x x back into the second equation, we see that 3 + 5 8 + y = 1 2 ( 1 + 5 4 ) 3 + 5 8 + y = 2 1 + 5 3 + 5 8 + y = 5 1 2 y = 5 1 2 3 + 5 8 = 3 5 7 8 \begin{aligned}\dfrac{3+\sqrt{5}}{8}+y&=\dfrac{1}{2\left(\dfrac{1+\sqrt{5}}{4}\right)}\\ \dfrac{3+\sqrt{5}}{8}+y&=\dfrac{2}{1+\sqrt{5}}\\ \dfrac{3+\sqrt{5}}{8}+y&=\dfrac{\sqrt{5}-1}{2}\\ y&= \dfrac{\sqrt{5}-1}{2}-\dfrac{3+\sqrt{5}}{8}\\ &= \dfrac{3\sqrt{5}-7}{8}\end{aligned}

Thus, x y = ( 3 + 5 8 ) ( 3 5 7 8 ) = 3 + 5 32 \begin{aligned}xy&=\left(\dfrac{3+\sqrt{5}}{8}\right)\left(\dfrac{3\sqrt{5}-7}{8}\right)\\ &= \dfrac{-3+\sqrt{5}}{32}\end{aligned}

Thus our final answer is 3 + 5 + 32 = 34 -3+5+32=\boxed{34} and we are done.

I have no idea how I managed to get a unique real solution with this crazy system of equations, but I did. I was just playing around with another concept, and it just kind of went downhill and I ended up with this.

Daniel Liu - 7 years ago

I did pretty much the same thing, but ended up squaring both sides of 4 x 2 = 1 2 x , 4x-2=\frac{1}{2\sqrt{x}}, and got lucky with the rational root theorem on the resulting cubic.

Jon Pentland - 7 years ago
Gacon Noname
Jun 6, 2014

For me,

a = x + y

b = y - x

\Rightarrow y 2 + 2 y = x 2 2 x + x < = > a 2 ( b + 2 ) = 1 2 ( 1 ) y^2 + 2y = x^2 -2x+ \sqrt{x} <=> a^2 (b+2)= \frac{1}{2} (1)

\Rightarrow x + y = 1 2 x < = > a 2 ( a b ) = 1 2 ( 2 ) x + y = \frac{1}{2\sqrt{x}} <=> a^2(a - b) = \frac{1}{2} (2)

( 1 ) ( 2 ) = > x = 3 + 5 8 ; y = 3 5 7 8 (1) - (2) => x = \frac{3 + \sqrt{5}}{8} ; y = \frac{3\sqrt{5} -7}{8}

\Rightarrow x y = 3 + 5 32 xy = \frac{-3 + \sqrt{5}}{32}

\Rightarrow
a + b + c = 34 a + b + c = \boxed{34}

I do not understand your third line. What did you do with x x x \sqrt{x} ?

Calvin Lin Staff - 7 years ago

Log in to reply

sorry, I forgot "plus", thank you !

Gacon Noname - 7 years ago

Yes. (1) + (2) and first solve cubic of a, then get b from (1). This gives x,y.

Niranjan Khanderia - 7 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...